The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1109/access.2019.2932991
|View full text |Cite
|
Sign up to set email alerts
|

Active Probability Backpropagation Neural Network Model for Monthly Prediction of Probabilistic Seismic Hazard Analysis in Taiwan

Abstract: In this study, an active probability backpropagation neural network model (PBNNM) was built by training a backpropagation neural network (BPNN) to predict the probability distribution of the probabilistic seismic hazard analysis (PSHA) monthly. The four-layered BPNN framework was determined using training data that were obtained from an earthquake catalogue for the time period of 1990-2015 (Taiwan Standard Time, TST). The studied region was divided into 500 small grids, each 0.2 • × 0.2 • in size, which is app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…A four-layered BPNN with two hidden layers was employed based on the error backpropagation (EBP) algorithm (Omatu et al 2018;Lin and Chiou 2019), which is a technology of artificial intelligence (AI), shown in Figure 5. The Levenberg-Marquardt algorithm (LMA) was used as the EBP algorithm because it is a more commonly used and well-established method than other EBP algorithms for use in general nonlinear problems (Lera and Pinzolas, 2002;Mammadli, 2017).…”
Section: Backpropagation Neural Networkmentioning
confidence: 99%
“…A four-layered BPNN with two hidden layers was employed based on the error backpropagation (EBP) algorithm (Omatu et al 2018;Lin and Chiou 2019), which is a technology of artificial intelligence (AI), shown in Figure 5. The Levenberg-Marquardt algorithm (LMA) was used as the EBP algorithm because it is a more commonly used and well-established method than other EBP algorithms for use in general nonlinear problems (Lera and Pinzolas, 2002;Mammadli, 2017).…”
Section: Backpropagation Neural Networkmentioning
confidence: 99%
“…5), where J = K = 10. Some researchers have indicated that a neural network with two hidden layers and few neurons can replace a network with numerous neurons in one hidden layer (Lin et al, 2018;Lin and Chiou, 2019;Chu et al, 2020). The training data were used to train the BPNN.…”
Section: Validation By Two Back-propagation Neural Network (Bpnn) Modelsmentioning
confidence: 99%
“…(2) For the first BPNN model, all the first principal eigenvalues of the B2DPCA (Fig. 3a), with random noise added in the range of 0-0.5 (Chen et al, 2013) as target outputs, and their corresponding grids forming a 20 × 30 input matrix of positions 1) in the studies of Lin et al (2018) and Lin & Chiou (2019) as the training inputs to form the training data. The largest principal eigenvalues were considered to indicate the TIDs.…”
Section: Validation By Two Back-propagation Neural Network (Bpnn) Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the development of artificial intelligence (AI) technology offers more possibilities for scientific assessments of geo-hazards risks. Numerous machine learning models, such as decision tree (DT) [23], support vector machine (SVM) [24], artificial neural network (ANN) [25], BP-artificial neural network (BP-ANN) [26], and Bayesian network (BN) models [27], have been applied for geo-hazards risk assessments. Among them, the SVM model, which is an efficient and reliable AI algorithm, has a very strong nonlinear processing ability and is one of the significant methods in risk assessment [28].…”
Section: Introductionmentioning
confidence: 99%